Teachers' Techniques in Developing of Akhlaq and Values in the Students - Othman, Mohamad Khairi Haji; Khalid, Rozalina; Puteh, Alis; Rahim, Fauziah Abd; Yusoff, Mohd. Zailani Mohd; Kasa, Muhamad Dzahir; Baharuddin, Nurfaizah (International Review of Management and Marketing, 2016)
Akhlaq and moral values among students who want to be born by the national education system can be achieved through the implementation of the inculcation of noble values in the teachings. Therefore, this article presents the findings related to the the students' perception of the techniques of the inculcation of noble values during classroom instructions. This descriptive survey study approach was conducted in one of the schools in the district of Kuala Muda/Yan in Kedah. A total number of Forms 4 and 2 students were selected as the respondents to complete the questionnaire. The study findings found that based on students' perception, there were five techniques that gained overall moderately high mean value, namely modelling, lecture, discussion, positive reinforcement and negative reinforcement. Meanwhile, other techniques were at medium low level. In summary, this study has shown that certain application techniques in instilling values should be practiced by teachers towards to increase students' moral understanding and development towards realizing the National Education Philosophy and the Malaysian Education Blueprint 2013 – 2025 in the context of producing human capital that are stable and harmony. Keywords: Development; Akhlaq; Values; Application;Technique JEL Classifications: A21, L29